ChemInform Abstract: 4‐Position‐Selective C—H Perfluoroalkylation and Perfluoroarylation of Six‐Membered Heteroaromatic Compounds. Issue 46 (October 2016) - Nagase, Masahiro; Kuninobu, Yoichiro; Kanai, Motomu
Abstract: Perfluoroalkylation of six‐membered N‐heterocycles proceeds regioselectively at the position para to the ring‐nitrogen.